Idarucizumab since FDA approval: Use in the real-world - Ebinger, Joseph; Granger, Christopher B.; Zhu, Alexander; Chang, Allison; Henry, Timothy D. (The American heart journal, 2017)
A 2017 updated cohort analysis of 503 patients demonstrated similar results, although the time to cessation of bleeding was improved at 2.5 hours.11 A review of the literature demonstrates limited data, with the largest case series to date including only 11 patients.12 As such, information on the use of idarucizumab in general practice outside of the research setting is lacking, leaving practitioners without a clear understanding of how frequently or in what circumstances the drug is being used.The initial and full cohort studies contained no control arms and did not address the documented difference between the normalization of coagulation studies in phase 1 trials and the nearly 12 hour time to cessation of bleeding in a clinical setting.10,13 Even if the updated cohort data, demonstrating a 2.5 hour time to cessation of bleeding is correct, this represents a lengthy gap between treatment and resolution of life threatening bleeding.[...]other studies have indicated that dabigatran's use has decreased compared with the other DOACs, despite the emergence of idarucizumab.1 By comparison, there were 317.1 prescriptions per month for warfarin during the same period.Temporal trends 2011-2015 in Denmark, Sci Rep, Vol. 6, 2016, 31477 2., J. Stangier, H. Stahle, K. Rathgen, Pharmacokinetics and pharmacodynamics of dabigatran etexilate, an oral direct thrombin inhibitor, are not affected by moderate hepatic impairment, J Clin Pharmacol, Vol. 48, Iss. 12, 2008, 1411-1419 3., J. Stangier, K. Rathgen, H. Stahle, Influence of renal impairment on the pharmacokinetics and pharmacodynamics of oral dabigatran etexilate: an open-label, parallel-group, single-centre study, Clin Pharmacokinet, Vol. 49, Iss. 4, 2010, 259-268 4., G.J. Hankey, J.W. Eikelboom, Dabigatran etexilate: a new oral thrombin inhibitor, Circulation, Vol. 123, Iss. 13, 2011, 1436-1450 5., J. van Ryn, J. Stangier, S. Haertter, Dabigatran etexilate--a novel, reversible, oral direct thrombin inhibitor: interpretation of coagulation assays and reversal of anticoagulant activity, Thromb Haemost, Vol. 103, Iss. 6, 2010, 1116-1127 6., R. Alikhan, R. Rayment, D. Keeling, The acute management of haemorrhage, surgery and overdose in patients receiving dabigatran, Emerg Med J, Vol. 31, Iss. 2, 2014, 163-168 7., R. Kumar, R.E. Smith, B.L. Henry, A Review of and Recommendations for the Management of Patients With Life-Threatening Dabigatran-Associated Hemorrhage: A Single-Center University Hospital Experience, J Intensive Care Med, Vol. 30, Iss. 8, 2015, 462-472 8., W.E. Dager, R.C. Gosselin, A.J. Roberts, Reversing dabigatran in life-threatening bleeding occurring during cardiac ablation with factor eight inhibitor bypassing activity, Crit Care Med, Vol. 41, Iss. 5, 2013, e42-46 9., D.N. Chang, W.E. Dager, A.I. Chin, Removal of dabigatran by hemodialysis, Am J Kidney Dis, Vol. 61, Iss. 3, 2013, 487-489 10., C.V. Pollack Jr., P.A. Reilly, J. Eikelboom, Idarucizumab for Dabigatran Reversal, N Engl J Med, Vol. 373, Iss. 6, 2015, 511-520 11., C.V. Pollack Jr., P.A. Reilly, J. van Ryn, Idarucizumab for Dabigatran Reversal - Full Cohort Analysis, N Engl J Med, Vol. 377, Iss. 5, 2017, 431-441 12., M.R. Vosko, C. Bocksrucker, R. Drwila, Real-life experience with the specific reversal agent idarucizumab for the management of emergency situations in dabigatran-treated patients: a series of 11 cases, J Thromb Thrombolysis, Vol. 43, Iss. 3, 2017, 306-317 13., P.A. Reilly, J. van Ryn, O. Grottke, Idarucizumab, a specific reversal agent for dabigatran: mode of action, pharmacokinetics and pharmacodynamics, and safety and efficacy in phase 1 subjects, Am J Emerg Med, Vol. 34, Iss. 11S, 2016, 26-32 14., L. Rosenberg, G. Gerstrom, M. Nybo, Idarucizumab for Reversal of Dabigatran Prior to Acute Surgery: A Schematic Approach based on a Case Report, Basic Clin Pharmacol Toxicol, Vol. 120, Iss. 4, 2017, 407-410 15., T.B. Braemswig, C.C. Eschenfelder, C.H. Nolte, Emergency lumbar puncture in a patient receiving dabigatran after antagonization with idarucizumab - A case report, Am J Emerg Med, Vol. 35, Iss. 4, 2016, 662.e3-662.e4 16., R.S. Henderson Jr., S. Deshpande, B. Williams, Idarucizumab for Dabigatran Reversal in Emergency Type-A Aortic Dissection, J Cardiothorac Vasc Anesth, 2016 17., P. Mazur, T. Darocha, G. Filip, Idarucizumab for dabigatran reversal in patients with atrial fibrillation undergoing emergency surgery for acute aortic syndrome, Pol Arch Med Wewn, Vol. 126, Iss. 7-8, 2016, 579-581 18., A.P. Steele, J.A. Lee, W.E. Dager, Incomplete dabigatran reversal with idarucizumab, Clin Toxicol, 2017, 1-3 19., M. Shoeb, M.C. Fang, Assessing bleeding risk in patients taking anticoagulants, J Thromb Thrombolysis, Vol. 35, Iss. 3, 2013, 312-319 20., P.G. Venkatesh, B. Njei, M.R. Sanaka, Risk of comorbidities and outcomes in patients with lower gastrointestinal bleeding - a nationwide study, Int J Colorectal Dis, Vol. 29, Iss. 8, 2014, 953-960